2022
DOI: 10.1038/s41467-022-32627-z
|View full text |Cite
|
Sign up to set email alerts
|

scRNA-seq of gastric tumor shows complex intercellular interaction with an alternative T cell exhaustion trajectory

Abstract: The tumor microenvironment (TME) in gastric cancer (GC) has been shown to be important for tumor control but the specific characteristics for GC are not fully appreciated. We generated an atlas of 166,533 cells from 10 GC patients with matched paratumor tissues and blood. Our results show tumor-associated stromal cells (TASCs) have upregulated activity of Wnt signaling and angiogenesis, and are negatively correlated with survival. Tumor-associated macrophages and LAMP3+ DCs are involved in mediating T cell act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 70 publications
1
52
0
Order By: Relevance
“…In gastric cancer, LAMP3+ DCs were predicted to deliver attracting and activating signals to lymphocytes. However, LAMP3+ DCs inhibited anti-tumor T cell activity through a high expression of PD-L1 ( 31 ). In lymph node metastasized tumors, LAMP3+ DCs showed a stronger interaction with Tregs to enhance immunosuppression ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, LAMP3+ DCs were predicted to deliver attracting and activating signals to lymphocytes. However, LAMP3+ DCs inhibited anti-tumor T cell activity through a high expression of PD-L1 ( 31 ). In lymph node metastasized tumors, LAMP3+ DCs showed a stronger interaction with Tregs to enhance immunosuppression ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 76 ) performed single-cell sequencing on a variety of tumor-infiltrating T cells, including gastric cancer and esophageal cancer, and found that the exhausted T cells were mainly from effector memory T cells and tissue-resident T cells. Recent study has found that the exhaustion of CD8 + T cells is accompanied by an increase in the number of Tc17 cells with poor cytolytic capacity ( 77 ).The scRNA-seq of gastric tumor also showed Tc17 exhaustion pathway originating from Trm ( 78 ). Another single-cell sequencing results showed that Trm cells could be divided into three subsets: Hobit-enriched CD103 hi PD-1 lo Trm, Granzyme K-enriched CD103 lo PD-1 hi Trm, and CD103 hi PD-1 hi CTLA hi LAG3 hi TIGIT hi Trm, while the last subset is considered as exhaustion-related subtype ( 79 ).…”
Section: Overview Of Tissue-resident Memory T Cellsmentioning
confidence: 99%
“…Specifically in digestive system cancers, TAMs are similarly thought to have mutual modulation with T cells, including but not limited to blocking the recruitment and priming of T cells and resulting in T-cell exclusion within the TME. In GC, TAMs and LAMP3 + dendritic cells (DCs) are involved in mediating T-cell activity and form intercellular interaction hubs with tumor-associated stromal cells[ 37 ]. IL-10 + TAM infiltration yielded an immunoevasive TME featured by Treg cell infiltration and CD8 + T-cell dysfunction[ 38 ].…”
Section: Tam Status In Tumorsmentioning
confidence: 99%